(796) Operations Research on National Planning بحوث العمليات في التخطيط الوطني - Dessouky, Mohamed I. (INP, 2024)
This paper aims at reviewing some interesting applications of operations research concepts and techniques to problems of national planning, and evaluating the advantages gained and the difficulties encountered in the use of these techniques. The paper is not intended to be a comprehensive survey of the subject, a task which would cover several large volumes. It is rather an investigation, through a number of practical example of the potentialities and limitations of such applications, drawing mainly on experiences in the U.A.R.